Human and Animal Viruses in Food (Including Taxonomy of Enteric Viruses) - Greening, Gail E. (Viruses in Foods, 2016)
In recent years, there has been an increase in the incidence of foodborne diseases worldwide, with viruses now being recognized as a major cause of these illnesses. The most common viruses implicated in foodborne disease are enteric viruses, which are found in the human gastrointestinal tract, excreted in human feces and transmitted by the fecal-oral route. Many different viruses are found in the gastrointestinal tract but not all are recognized as foodborne pathogens. The diseases caused by enteric viruses fall into three main types: gastroenteritis, enterically transmitted hepatitis, and illnesses that can affect other parts of the body such as the eye, the respiratory system and the central nervous system leading to conjunctivitis, poliomyelitis, meningitis and encephalitis. Viral pathogens excreted in human feces include noroviruses, sapoviruses, enteroviruses, adenoviruses, hepatitis A virus (HAV), hepatitis E virus (HEV), rotaviruses, and astroviruses. Most of these viruses have been associated with foodborne disease outbreaks. Noroviruses and HAV are commonly identified as foodborne causes of gastroenteritis and acute hepatitis, respectively.